O etiquetamento dos negros no reconhecimento de pessoas como fator de seletividade penal : o desvirtuamento da prova do reconhecimento de pessoas sob o enfoque da teoria do labelling approach no contexto racista - Gomes, Paolo Diego Dias Moura (2024)
The present research addresses the theory of labelling approach in terms of personal and photographic recognition, provided for in article 226 of the Code of Criminal Procedure, in order to analyze the secondary criminalization that is built on certain groups, mostly the most vulnerable, predominantly those of black or brown color, due to the non-conforming use of said evidentiary institute. The panorama of the labelling theory was being drawn and the legal experiences were formed in the positivist culture of applying traditional methods of control and interpretation, instead of working to solve this problem, they consolidated the issue of the label of criminals attributed to the poor and blacks, linking the problem to the criminal procedural sphere. The use of personal and photographic recognition evidence, without due observance of legal procedures, in the unbridled eagerness to promote a judicial conviction of individuals with characteristics linked to the phenotype, is an example of such a picture. Much has been discussed about the proof of recognition of persons, provided for in article 226 of the Code of Criminal Procedure, its probative value from a legal point of view, in view of the various cases faced in the sphere of the Judiciary and the change in the position of the Superior Court of Justice with the judgment of Habeas Corpus No. 598,886, reported by Justice Rogério Schietti. The criticism made from the legal and juridical point of view sometimes stems from the need to be cautious in valuing the recognition of people as an evidentiary instrument capable of justifying the conviction of the individual against whom the state punitive system imputes a certain crime, given their great susceptibility to failures by human memory, sometimes linked to the racist context of the Brazilian legal system, in addition to the risks of miscarriage of justice when considering it as the basis for conviction, dissociated from other concrete evidence. What the essay text defends what it will argue is that the non-conformity of the procedural rite of proof of personal and photographic recognition constitutes a posture resulting from the social control exercised by the state sphere formed by the selective and discriminatory tradition of people considered deviant, against whom attitudes have been adopted that are normally different from those natural postures that one would have with any person.